A quantitative comparison of physiologic indicators of cardiopulmonary resuscitation quality: Diastolic blood pressure versus end-tidal carbon dioxide. (July 2016) - Morgan, Ryan W.; French, Benjamin; Kilbaugh, Todd J.; Naim, Maryam Y.; Wolfe, Heather; Bratinov, George; Shoap, Wesley; Hsieh, Ting-Chang; Nadkarni, Vinay M.; Berg, Robert A.; Sutton, Robert M.
Abstract: Aim: The American Heart Association (AHA) recommends monitoring invasive arterial diastolic blood pressure (DBP) and end-tidal carbon dioxide (ETCO2 ) during cardiopulmonary resuscitation (CPR) when available. In intensive care unit patients, both may be available to the rescuer. The objective of this study was to compare DBP vs. ETCO2 during CPR as predictors of cardiac arrest survival. Methods: In two models of cardiac arrest (primary ventricular fibrillation [VF] and asphyxia-associated VF), 3-month old swine received either standard AHA guideline-based CPR or patient-centric, BP-guided CPR. Mean values of DBP and ETCO2 in the final 2 min before the first defibrillation attempt were compared using receiver operating characteristic curves (area under curve [AUC] analysis). The optimal DBP cut point to predict survival was derived and subsequently validated in two independent, randomly generated cohorts. Results: Of 60 animals, 37 (61.7%) survived to 45 min. DBP was higher in survivors than in non-survivors (40.6 ± 1.8 mmHg vs. 25.9 ± 2.4 mmHg; p  < 0.001), while ETCO2 was not different (30.0 ± 1.5 mmHg vs. 32.5 ± 1.8 mmHg; p  = 0.30). By AUC analysis, DBP was superior to ETCO2 (0.82 vs. 0.60; p  = 0.025) in discriminating survivors from non-survivors. The optimal DBP cut point in the derivation cohort was 34.1 mmHg. In the validation cohort, this cut point demonstrated a sensitivity of 0.78, specificity of 0.81, positive predictive value of 0.64, and negative predictive value of 0.89 for survival. Conclusions: In both primary and asphyxia-associated VF porcine models of cardiac arrest, DBP discriminates survivors from non-survivors better than ETCO2 . Failure to attain a DBP >34 mmHg during CPR is highly predictive of non-survival.